Potret kesopanan anak Indonesia dalam film-film animasi Indonesia - Karim, Ahmad Abdul; Martutik, Martutik; Susanto, Gatut (Universitas Mulawarman, 2025)
The urgency of this study lies in the significance of children's viewing media, particularly animated films, as a means of character development and the internalization of politeness values aligned with Indonesian cultural norms. Amid the proliferation of media content that neglects educational aspects, local animated films emerge as a potential alternative for reinforcing character education. This study aims to reveal representations of politeness among Indonesian children in five locally produced animated films released between 2015–2021: Diva The Series (2015), Cerita Eza dan Adi (2017), Nussa (2018), Sampah Sandi (2019), and Riko The Series Season 2 (2021). Employing a pragmatic approach, the study applies Leech's politeness principle theory. Data collection techniques include observation, attentive listening, note-taking, and literature review. The data were analyzed through a process of selection, interpretation, and conclusion. The findings indicate that politeness is represented through character interactions, such as courteous speech, respectful attitudes, and the use of polite language. Each film emphasizes different maxims, with the Tact Maxim emerging as the most dominant. The study concludes that Indonesian animated films serve not only as entertainment but also as educational media that instill politeness values consistent with local cultural and social norms.